Elastic and inelastic scattering for the 11B+58Ni system: Target and projectile reorientation effects - Deshmukh, N. N.; Guimaraes, V.; Crema, E.; Abriola, Daniel Hugo; Arazi, Andres; de Barbará, Ezequiel; Capurro, Oscar Ángel; Cardona, Maria Angelica; García Gallardo, Jorge Antonio; Hojman, Daniel Leonardo; Marti, Guillermo; Pacheco, Alberto Jorge; et al. (American Physical Society, 2015)
Fil: Deshmukh, N. N.. Universidade de Sao Paulo; Brasil